Economic inequality and the value of nature - Moritz A. Drupp; Jasper N. Meya; Stefan Baumgärtner; Martin F. Quaas (Kiel University, Department of Economics, 2017)
Understanding what influences the value of nature is crucial for informing environmental policy. From a sustainability perspective, economic valuation should not only seek to determine willingness to pay for environmental goods to devise an efficient allocation of scarce resources, but should also account for distributional effects to ensure justice. Yet, how economic inequality affects the value of non-market environmental goods remains understudied. Combining recently developed theoretical results with empirical evidence we show that more equal societies have a higher valuation for environmental public goods and that non-market benefits of environmental policy accrue over-proportionally to poorer households. On this ground, we identify a number of fruitful areas for future research and discuss implications for environmental valuation, management and policy-making. We conclude that environmental valuation should explicitly account for economic inequality, and that encompassing assessments of the distributional effects of environmental policies must consider the distribution of non-market environmental benefits.
Keywords: Q51; Q01; Q57; Q56; H43; 330; nature conservation; environmental goods; valuation; willingness to pay; income inequality; distribution